INFLUENCE OF CITRIC ACID, GINGER EXTRACT AND STORAGE PERIOD ON FRUIT QUALITY OF LOCAL ORANGE (Citrus sinensis L. Osbeck) - Al-Hajani, Rezan M. A.; Haded, N. N. F.; Al Bamarny, S. F. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was carried out on fruit of local orange (Citrus sinensis L. Osbeck) grown at private orchard Diyala governorate / Iraq, to study the effect of dipped fruits for 10 min in (0, 1, 2, 3% citric acid, 5 and 10% ginger) on fruit quality of orange during 65- and 105-days cold storage at 5+1 with 85- 90% RH. Dipping fruits in citric acid solution reduced fruit’s weight loss and decay. Ginger extract at 5 and 10% significantly reserved acidity, total sugar and sugar/acid ratio, also caused a reduction in fruit weight loss and fruit decay. There was a significant decreases in fruits peel carotene and an increases in vitamin C, when fruits were treated with 5% ginger extract. Prolonging storage period from 65 to 105day significantly increased fruit total soluble solids, weight loss, total sugar, and fruit peel carotene but, reduced vitamin C and total acidity. The interaction between dip treatments and storage period had a significantly positive effect on the quality feature of fruit orange.